Casualty Care Simulator for Standalone VR - Proposing Areas of Consideration when Designing Casualty Care Simulators for Standalone VR Systems - Nordblom, Hannes; Stigson, Jonathan (My University, 2024)
VR is becoming a prominent tool in many fields. Military applications are no exception and VR is already used extensively in various military fields such as combat training and flight simulation, allowing learners to experience an environment resembling what they would encounter in real life. In this thesis, casualty care is explored by developing a simulator for a standalone VR system that teaches the users what steps to take when a squadmate amputates a limb resulting from a landmine explosion. The prototype was tested in a user study using participants (n = 13) with and without military backgrounds. The results from the quantitative data analysis showed that there was no statistically significant effect on any of the 28 dependent variables, most of which were primarily indicative of performance. The qualitative data analysis, supported by the quantitative data analysis, resulted in four design considerations that one should take into account when designing casualty care simulators for standalone VR systems.
Keywords: casualty care; virtual reality; hmd; standalone vr; military medicine